Lunch lady and the picture day peril - Krosoczka, Jarrett (Krosoczka, Jarrett. Lunch Lady, 2012)
When eccentric photographer Stefani DePino comes to Thompson Brook to take school pictures in the midst of an acne epidemic, Lunch Lady, Betty, and the Breakfast Bunch learn that Stefani is using them to break into the world of high fashion.